Innovation project management : methods, case studies, and tools for managing innovation projects - Kerzner, Harold (Wiley, 2019)
"Harold Kerzner has bridged innovation, project management, and strategic planning in Innovation Project Management to offer students and practicing professionals the tools, processes, and metrics needed to successfully manage innovation projects. By analyzing innovation from all sides, this compendium of innovation project management breaks down traditional project management methods and explains why and how innovation projects should be managed differently. This title includes exclusive insights from world-class organizations such as Airbus, Boeing, Deloitte, Hitachi, IBM, Siemens, and more. This is a must-have title for practicing project managers, as well as students in project management, innovation, and entrepreneurship programs. Each case study contains questions for discussion, and Instructors have access to extensive PowerPoint lecture slides by chapter and an Instructors Manual via the book's companion website"--